2013
DOI: 10.1021/es3041797
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Insights into the Involvement of Radicals in Triclosan Phototransformation

Abstract: The phototransformation of triclosan has been a matter of longstanding interest due to both its prevalence in the environment and the discovery of 2,8-dichlorodibenzodioxin as a photoproduct. In this study, photolysis of triclosan resulted in several primary photoproducts including the following: 2,8-dichlorodibenzodioxin (4%), 4,5'-dichloro-[1,1'-biphenyl]-2,2'-diol (10%), 5-chloro-2-(4-chlorophenoxy)phenol (0.5%), and 2,4-dichlorophenol (7%). Trapping studies using d8-isopropanol showed deuterium incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 46 publications
5
62
0
Order By: Relevance
“…Generally, ECs in natural surface waters can be transformed through biodegradation, hydrolysis, and photolysis. However, biodegradation and hydrolysis have been reported to be ineffective for TCS (Singer et al, 2002), and photolysis has been found to be an important TCS transformation process in surface waters (Anger et al, 2013;Kliegman et al, 2013). Therefore, the most important factor controlling the fate of TCS in aquatic environments is likely to be its photolysis (Boreen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, ECs in natural surface waters can be transformed through biodegradation, hydrolysis, and photolysis. However, biodegradation and hydrolysis have been reported to be ineffective for TCS (Singer et al, 2002), and photolysis has been found to be an important TCS transformation process in surface waters (Anger et al, 2013;Kliegman et al, 2013). Therefore, the most important factor controlling the fate of TCS in aquatic environments is likely to be its photolysis (Boreen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, as well as direct photolysis (Anger et al, 2013;Latch et al, 2003;Wong-Wah-Chung et al, 2007), the phototransformation of TCS includes photosensitized transformation (Wong-Wah-Chung et al, 2007), and reaction with reactive species (RSs). Research in this area has mainly been focused on identifying and quantifying the polychlorinated dibenzo-p-dioxin (called "dioxin" in the rest of this paper) photoproducts that can be formed and the transformation pathways in the direct photolysis and photosensitized transformation of TCS (Anger et al, 2013;Kliegman et al, 2013;Latch et al, 2003Latch et al, , 2005Mezcua et al, 2004;WongWah-Chung et al, 2007 formed and are constantly present at low concentrations in natural waters (Dong and Rosario-Ortiz, 2012;Vione et al, 2006). Of these, OH is a well-known highly reactive oxidant that plays an important role in the transformation of a wide spectrum of ECs in natural waters (Dong and Rosario-Ortiz, 2012;Wenk et al, 2011) because of the high absolute bimolecular rate constants with ECs (An et al, 2010a(An et al, , 2010bBuxton et al, 1988;Fang et al, 2013;Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since the calculations generally suppose an isolated molecule in a vacuum, a solvation effect has been taken into account in some cases, indirectly by using a polarized continuum 28,33,50) or Onsager's cavity model, 70,73) or directly by introducing water molecules into the calculations. 49) A bond liable to be photocleaved 53,73,74) together with the preference of a homolytic or heterolytic mechanism 33,75) can be conveniently evaluated by its dissociation energy. Electronic excitation generally changes the electronic overlap population between two atoms participating in bond cleavage or formation, and the changes can be used as a photochemical index.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…4) In the case of triclosan rearranging at 300 nm to the diphenyl derivative, a different biradical mechanism was proposed via one-electron reduction, followed by the release of Cl − . 75) Cyclohexene oxime herbicides such as alloxydim 119) generally undergo photo-induced N-O cleavage to form the corresponding imines. The succeeding hydrolysis produced the ketone derivative in the case of tralkoxydim.…”
Section: Ethersmentioning
confidence: 99%
“…However, some questions have drawn our attention. For example, dioxin derivatives, which have higher toxicity than TCS, were formed during photodegradation of TCS in aqueous solutions (Kliegman et al 2013). As to biodegradation, it was usually time-consuming and incomplete to remove TCS from wastewater because of its antimicrobial property (Ying et al 2007).…”
Section: Introductionmentioning
confidence: 99%